1997
DOI: 10.1111/j.1398-9995.1997.tb01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prevalence of skin prick test positivity to Alternaria and Cladosporium in patients with suspected respiratory allergy

Abstract: D'Amato G, Chatzigeorgiou G, Corsico R, Gioulekas D, Jäger L, Jäger S, Kontou‐Fili K, Kouridakis S, Liccardi G, Meriggi A, Palma‐Carlos A, Palma‐Carlos ML, Pagan Aleman A, Parmiani S, Puccinelli R Russo M, Spieksma FThM, Torricelli R, Wüthrich B. Evaluation of the prevalence of skin prick test positivity to Alternaria and Cladosporium in patients with suspected respiratory allergy. A European multicenter study promoted by the Subcommittee on Aerobiology and Environmental Aspects of Inhalant Allergens of the Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 13 publications
1
52
1
Order By: Relevance
“…Moulds sensitisation prevalence was 11.2 %, a similar value to those founded by other authors 23,32 . However this result is very discrepant from other portuguese studies [14][15][16]33,34 showing lower values (3 %).…”
Section: Discussioncontrasting
confidence: 56%
“…Moulds sensitisation prevalence was 11.2 %, a similar value to those founded by other authors 23,32 . However this result is very discrepant from other portuguese studies [14][15][16]33,34 showing lower values (3 %).…”
Section: Discussioncontrasting
confidence: 56%
“…Earlier work implicates Alternaria exposure as a cause of asthma exacerbation in sensitized individuals although its role during thunderstorms has not been investigated [27±29]. Sensitization to Cladosporium is associated with diagnosis of asthma and rhinitis [30,31] but the possible importance of the fungus in triggering acute asthma exacerbation has not been previously reported. Aerobiological studies show that levels of Cladosporium spores in ambient air may be amongst the highest of the fungi and its role in causing exacerbations of asthma deserves further investigation [32,33].…”
Section: Thundmentioning
confidence: 99%
“…Some studies have shown that the majority of the skin prick test positive patients are less than 10 years old [18]. Rhinitis was the most common symptom in positive skin prick test persons whether associated or not with asthma and or conjunctivitis [19]. The main contribution of this study is that Mycoplasma spp.…”
Section: Discussionmentioning
confidence: 78%